2021
DOI: 10.1001/jama.2021.2133
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Treatment of Valvular Heart Disease

Abstract: ImportanceMore than 40 million people are living with either mitral or aortic valve disease worldwide, and more than 180 000 heart valve replacement surgeries are performed each year in the US. Transcatheter valve repair has emerged as an important therapeutic option for patients who are candidates for heart valve replacement.ObservationsAll transcatheter valve therapies involve a multidisciplinary team of interventional cardiologists, cardiothoracic surgeons, radiologists, echocardiographers, nurses, and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 50 publications
0
55
0
Order By: Relevance
“…[ 21 ] The majority of TAVR procedures are performed through a transfemoral access (98.2%) in China, which is higher than that in other registries or national databases. [ 14 , 22 ] This could be because TAVR took off late in China; consequently, operators favor a more established and safer route of transfemoral access. This trend is mirrored in the Society of Thoracic Surgeons (STS)/TVT database, which showed that before 2013, transfemoral access was adopted in only 57.08%, and by 2019, the figure reached 95.26% ( P trends < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] The majority of TAVR procedures are performed through a transfemoral access (98.2%) in China, which is higher than that in other registries or national databases. [ 14 , 22 ] This could be because TAVR took off late in China; consequently, operators favor a more established and safer route of transfemoral access. This trend is mirrored in the Society of Thoracic Surgeons (STS)/TVT database, which showed that before 2013, transfemoral access was adopted in only 57.08%, and by 2019, the figure reached 95.26% ( P trends < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of rivaroxaban compared to warfarin in patients with both AF and a bioprosthetic mitral valve, the NOAC was reported to be noninferior to warfarin in terms of the primary outcome at 12 months of either death, major cardiovascular events or major bleeding [ 55 ]. Transcatheter treatment of valvular heart disease is gaining increasing utilization in recognition of enhanced safety [ 56 ]. Transcatheter aortic valve implantation (TAVI) can be performed with either a balloon-expandable or self-expanding valve, and is performed percutaneously.…”
Section: Valvular Cardiac Disease and The Brainmentioning
confidence: 99%
“…For lower risk patients, the rate of death from any cause, stroke or rehospitalization was 8.5% with TAVI and 15.1% for surgical aortic valve replacement according to one study [ 57 ]. For mitral regurgitation, there is now an FDA-approved mitral transcatheter edge-to-edge repair device for higher risk patients with severe symptomatic mitral regurgitation [ 56 ]. In the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients (COAPT) study [ 58 ], intervention resulted in annualized rate of hospital admissions of 35.8% compared to 67.9% for those who received medical therapy alone.…”
Section: Valvular Cardiac Disease and The Brainmentioning
confidence: 99%
“…Transcatheter edge-to-edge repair (TEER) of the mitral valve (MV) caused a revolution in MR treatment when the MitraClip system (Abbott) was approved in Europe in 2008 for both indications, i.e., SMR and FMR, whereas it was approved in 2013 in the United States and only for SMR [ 3 ]. The treatment was primarily intended for FMR patients with very high operative risk, but it was soon adopted as an efficient therapeutic option in SMR patients with unacceptable operative risk [ 4 , 5 ]. More than one decade later, a new system for MV TEER, the PASCAL device (Edwards), was approved in Europe, but still not in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Over more than one decade, our knowledge about MV repair has significantly increased; however, most published studies have been focused on the outcomes of MR patients after this procedure [ 4 , 5 ]. The demographic and clinical characteristics of SMR and FMR patients who underwent this procedure have been significantly less investigated.…”
Section: Introductionmentioning
confidence: 99%